Being Aggressive An Interpretative Phenomenological Analysis of Kung Fu Practitioners’ Experience of Aggression (Existential Analysis: Journal of the Society for Existential Analysis, 2009)
Whilst human aggression is discussed widely in psychological literature, it is often addressed from the standpoint of positivistic science which suggests it is outside the control of the somewhat passive individual, who requires interventions to prevent or control it, implying that all aggression is pathological. Whilst this has its uses, it provides only a one-sided view, and contributes little to a fuller understanding of the experience of aggression. This paper begins to address this 'gap' in the literature by presenting findings from an Interpretative Phenomenological Analysis into the experience of aggressive. The study reports data from semi-structured interviews with six martial arts practitioners and shows how participants described the process of learning to deal with a physical aggressor in training, the difficult feelings they had to confront (including their own fear and aggression), and the inner resources they drew upon during this process. In doing so, participants described achieving a state they called 'intent' which allowed them to deal with an aggressor with relative ease. In contrast to the current psychological literature, participants described themselves as active in engendering their own aggression, and outlined some of the more positive aspects that it played in their lives. Some of the questions this raises for practitioners, and areas for further research, are then discussed.
Keywords: Aggression; Critique; Health; Pathology